OPTIMALISASI PEMBINAAN NARAPIDANA SEBAGAI UPAYA PEMENUHAN HAK ASASI MANUSIA (HAM) DALAM PENCEGAHAN TERJADINYA RECIDIVE DI LEMBAGA PEMASYARAKATAN KELAS IIA TENGGARONG - Angga Cipto Biantoro (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT This study is entitled "LEGAL ASPECTS ON THE TRANSACTION OF NARCOTIC TRADING IN THE BORDER REGION BETWEEN THE REPUBLIC OF INDONESIA - MALAYSIA", under the guidance that I respect Mrs. Kunti Widayati, S.H., M.Hum as a Supervisor 1 and Mr. Sukindar, S.H., M.H as the Supervisor II.This research is entitled "Optimizing the Development of Prisoners as an Effort to Fulfill Human Rights (Ham) in Preventing the Occurrence of Recidives in the Class Iia Tenggarong Correctional Institution".The purpose to be achieved in this study is to determine the form of implementation in the development of prisoners as an effort to prevent recidivism crimes in accordance with the human rights provisions that apply in Tenggarong class IIA prisons and the obstacles faced in the implementation of coaching in class IIA Tenggarong prisons.This research was conducted at Class IIA Tenggarong Prison. The approach method used in the preparation of this thesis is an empirical juridical approach. The data collection technique is done by interview, observation, questionnaire, and documentation. Furthermore, the data obtained from the results of research in the field were analyzed using quantitative analysis studies.Based on the results of the study, the authors conclude that the factors that influence prisoners to commit repetition of crimes, namely: economic problems, social environment, lack of parental supervision, the role of information and technology developments that have a negative impact, lack of education and forms of guidance carried out by officers. Class IIA Tenggarong Prison in preventing the occurrence of a repeat offense. Class IIA Tenggarong Prison officers also provide training and skills training programs such as making handicrafts using used materials such as making ashtrays, cabinets, mirrors, newspaper photo frames, sewing guidance, fish farming guidance, motorbike repair guidance, iron fence making guidance. for inmates as a provision for working capital after serving his sentence.The implication of this research is that it is hoped that the guidance given to inmates is more optimal, it is necessary to collaborate with the community and it is expected to provide special guidance to recidivist prisoners. In order for coaching to run well, the human resources of correctional officers need to be added and improved so that they are sufficiently equipped to carry out their duties. Keywords: Development of Prisoners, Recidive, Correctional Institutions